Progress in the research of GPIIb/IIIa antagonists. (July 2015) - Xie, Zhouling; Cao, Chen; Feng, Sen; Huang, Jing; Li, Zhiyu
This review covers the recent advances in the development of small RGD (Arg-Gly-Asp sequence) containing peptides and their mimetics as potential antithrombotic agents. Glycoprotein IIb/IIIa (GPIIb/IIIa) antagonists include monoclonal antibodies, RGD peptides, peptide hybrids and nonpeptide mimetics. The current trend in the development of nonpeptide mimetics is clearly directed toward orally active and safe antithrombotic drug candidates. But several nonpeptide mimetics, being evaluated for their oral activity in human clinical trials, are currently not approved for clinical use due to poor safety profile. It is expected that newer and more effective nonpeptide mimetics will be developed in the near future.